2011
DOI: 10.1007/s11434-011-4564-2
|View full text |Cite
|
Sign up to set email alerts
|

Varying coefficient analysis for indeterminate species interactions with non-parametric estimation, exemplifying with a fig-fig wasp system

Abstract: Research on species interactions has generally assumed that species have a fixed interaction and therefore linear or non-linear parametric regression models (e.g. exponential, logistic) have been widely used to describe the species interaction. However, these models that describe the relationship between interacting species as a specific functional response might not be appropriate for real biological communities, for instance, in a chaotic system, when the species relationship varies among different situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, these theories assume that the interactions between members of the group are symmetrical, which makes it difficult to account for the uneven contributions often observed in natural systems. Asymmetric contributions to the common good have been observed in humans [9], bees [20], mole-rats [23], and a number of inter-specific mutualisms [15,17,26,30]. However, theoretical work has not shed light on how social asymmetries affect predicted patterns of volunteerism when members of the social group are related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these theories assume that the interactions between members of the group are symmetrical, which makes it difficult to account for the uneven contributions often observed in natural systems. Asymmetric contributions to the common good have been observed in humans [9], bees [20], mole-rats [23], and a number of inter-specific mutualisms [15,17,26,30]. However, theoretical work has not shed light on how social asymmetries affect predicted patterns of volunteerism when members of the social group are related.…”
Section: Discussionmentioning
confidence: 99%
“…In the VoD game, Archetti [7,18] has also demonstrated that relatedness strongly influences the likelihood that players will exhibit cooperative behavior. In fact, both the effects of asymmetry and relatedness may simultaneously coexist in many real systems, such as eusocial system of ants and bees [20], inter-specific mutualistic of the yuccas and the yucca moth [15] and the figs and the fig wasp [16,17,21,30]. Here, we sought to explore how asymmetry combined with relatedness affects the behaviors of individuals in cooperative social systems by recombining and extending the models of Diekmann [19] and Archetti [7,18].…”
Section: Asymmetric Volunteer's Dilemma Game With Relatednessmentioning
confidence: 99%
“…For details of the varying coefficient analysis model and the comparison between the varying coefficient method and traditional linear regression or generalized linear regression see the electronic supplementary material, online appendix or the paper by Shi et al . [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Probabilities for range expansion are now hampered in the current islands of Southeast Asia, sustaining populations in situ is becoming the only option [47]. Currently, conservationists are paying more attention to in situ small and fragmented populations of species, as these are the ones at the greatest risk of extirpation [53][54][55][56][57][58][59]. Specifically, small isolated populations are sensitive to genetic erosion.…”
Section: Conservation Implicationsmentioning
confidence: 99%